Factors that Influence Online Psychotherapeutic Relationship in Teachers Training College in the Lake Region, Kenya - Odera, Florence; Ochola, Jenipher; Kodero, Hesbon (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
Online technology emerged as a useful tool for psychotherapy practices in higher institution of learning. From 2014, the Ministry of Education provided internet technology facilities in public teacher training colleges. This was aimed at providing access to a wide range of educational material and facilities for educational guidance and counseling and psychotherapy practices. The purpose of this study was to identify the factors that influence online psychotherapeutic relationship between the counselor and the clients with a view of giving a critical perspective of evidence based approach for this practice. The objective of the study was to find out the factors influencing online psychotherapeutic relationship between the trainees and tutors in teacher training colleges in the Lake Region of Kenya. The population consisted of 327 participants. This included40 tutors, and 287 teacher trainees. Data was collected by use of semi-structured questionnaires and interview schedule. Data collected was analyzed by use descriptive statistics and presented qualitatively and quantitatively. That included percentages and frequency count. The finding of this study showed that 76% of the tutor counselors reported that feelings influenced them to introduce online psychotherapy practice. The other results indicated that honesty, and 80%stated that trust and emotional closeness influence their relationship. At the same time, 73% of the tutors counselors reported feelings and honesty was reported by 83% and 87% said trust and emotional closeness. But only 7% remained neutral. The findings of this study may assist the government, non-governmental organization and professional psychotherapists to allocate more resources for the development of online psychotherapeutic relationship in Teacher Training Colleges. Based on the research findings the study recommends that online psychotherapeutic relationship be strengthened in teacher training colleges.